2014
DOI: 10.1039/c4ra07589g
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free one-pot synthesis of amides using graphene oxide as an efficient catalyst

Abstract: Graphene oxide was found to be a highly efficient carbocatalyst for one-pot synthesis of amides from aromatic aldehydes and secondary amine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Moreover, the reusability of this catalyst was investigated up to six catalytic cycles in the synthesis of amide derivatives. Furthermore, the reaction mechanism of this reaction was suggested and discussed [76].…”
Section: Graphene Nanocomposites For Catalysismentioning
confidence: 99%
“…Moreover, the reusability of this catalyst was investigated up to six catalytic cycles in the synthesis of amide derivatives. Furthermore, the reaction mechanism of this reaction was suggested and discussed [76].…”
Section: Graphene Nanocomposites For Catalysismentioning
confidence: 99%
“…We think that the reaction may proceed through a radical as in pathway B; the unpaired electrons present at the edge of GO [51] react with the atmospheric oxygen to generate oxygen radical, which subsequently reacts with amine to generate aminyl radical. This aminyl radical can undergo a subsequent reaction with activated aldehyde to generate an alkoxy radical, leading to the formation of the corresponding amide product after hydrogen radical elimination [52].…”
Section: Mechanismmentioning
confidence: 99%
“…It is a single layer sheet with honeycomb like structure and possesses various oxygen containing functionalities such as SO 3 H, hydroxyl, epoxy, carboxyl and carbonyl groups at the edges and its basal plane 21 . These oxygen containing functionalities endows acidic and oxidizing nature in heterogeneous catalysis and hence graphene oxide has widely been used in oxidation, hydration, alcoholysis, Friedel-Craft reaction, Aldol condensation and Knoevenagel reaction, esterification, transesterification and glycerol esterification [22][23][24][25] . Recently X. Gao et al reported graphene oxide as a catalyst for complete glycerol esterification with 90.2 % combined selectivity preferably to 6 bioadditives diglycerol and triglycerol 22 .…”
Section: Introductionmentioning
confidence: 99%